SYSTEMS USING ENERGY SOLAR RADIATION - Velimir Šćekić; Saša Pušica; Sanja Marković (Journal of Engineering & Processing Management, 2011)
Energy is now one of the most important components of development and functioning of the economy and society in general. The development of civilization use different energy sources – fossil fuels and other energy sources like wind and water that are used to drive windmills, water mills and boats. Many countries begin the rationalization of energy consumption in the field, while applying more and more alternative energy sources (solar radiation, wind, etc.) would reduce its energy dependence. In line with this, this paper provides an overview of the system energy use sunlight as an aspect of rationalization of energy consumption.
Keywords: energy; radiation; heating